TRANScender: Proyecto de empoderamiento mediático y estrategias de comunicación para mujeres trans - Bustamante Santa Cruz, Brigitte Scarlette (2022)
TRANScender is a virtual spokesperson and media training workshop for the group of trans women Féminas. This seeks to provide tools and knowledge that enhance the skills of the participants to empower them to create new communication spaces and get involved in existing ones and thus contribute to the visibility of the transgender community in Peru.